Effect of Deposition Voltage on Layer Thickness, Microstructure, Cu/Ni Sheet Resistivity of Deposition Results by Magnetic Field Electroplating Assisted Technique - Wijanarka, Willi Anindita; Toifur, Moh (Indonesian Review of Physics (IRiP), 2020)
The purpose of this research is to make the Cu/Ni thin layer as an alternative to basic RTD materials through electroplating methods assisted by magnetic fields. Electroplating was carried out with variation in deposition voltage ranging from 1 to 5 V. The results of this study indicate that the deposition voltage applied to the coating affects the thickness, sheet resistivity, and microstructure of the coating. Thickness increases with increasing deposition voltage. The diffraction intensity and crystal size tend to increase with increasing deposition voltage. The distance between Bragg planes after the coating is almost equal for all samples. The highest sheet resistivity was obtained in the coating sample with a 4-volt deposition voltage.